47 MARKPAP® TEST MOVES INTO DOCTOR OFFICES. (1st March 2006) - Markovic, O.; Markovic, N.; Townsend, L.; Smith, W.; Hankins, D.; Cotic, M.; McJonathan, S.
Abstract : Introduction: MarkPap test is an emerging biomarker-based technology for the enhancement of the visibility of abnormal cells on Pap specimens. The biomarker, a specific isoenzyme configuration of cervical acid phosphatase, is present in abnormal cervical cells. Visualized with the MarkPap test, the biomarker appears as intracellular red granular deposit on modified bluish Papanicolaou background (counterstaining). The biomarker is flagging dysplastic, HPV-infected, and cancerous cells, so they could hardly be missed during screening, even by low-trained personnel. Normal epithelial cells are entirely negative. With the MarkPap Research Kit, the test can be performed in doctor's offices by a nurse. The microscopic images of suspicious "red-labeled" biomarker positive cells are then captured by a digital camera and transmitted into laboratories with qualified reviewers for evaluation (MarkPap Digital). Control slides are included in the kit. Methods: The MarkPap test is suited for both conventional Pap smears and liquid-based Pap. Details for the technical procedure are provided in the Kit Insert. MarkPap Research Kit, MarkPap Accessories (MarkPap Solution, Control Slides) and MarkPap Digital are described and illustrated at <http://bioscicon.com/markpapproducts.html >. Results: In a pilot study, we assembled an image acquisition module consisting of low-cost microscope and digital camera (GT Vision, Hagerstown, MD), barcode reader and image acquisition software, an image and data transferring module, and an image evaluation module. Using already processed MarkPap slides, catalogued in BioSciCon Slide Library, we proved the feasibility of the method. The quality of the images transferred to the laboratory allows evaluation to be performed. The entire time consisting of sample acquisition, slide processing, and evaluation may not exceed 3 hours. Conclusion: MarkPap test, performed with customer-friendly MarkPap Research Kit, can be done by a nurse in a doctor's office and images of suspicious red-labeled cells can be captured and transmitted in the cytopathology laboratory for evaluation. With MarkPap Digital, moving cervical cancer screening into doctor offices becomes reality with unprecedented benefit for all women in the world. Authors acknowledge the support provided by Dr. John Reiss, Saul Ewing, LLP, Philadelphia, PA. Technical assistance was provided by Ms. Milena Simic.